Physicochemical, Nutritional, and Antioxidant Properties in Seven Sweet Potato Flours - Zhang, Lin; Gao, Yan; Deng, Bowen; Ru, Weidong; Tong, Chuan; Bao, Jinsong (Frontiers in Nutrition, 2022)
Sweet potato flour is a key ingredient for the production of new food products worldwide, which imparts desired properties, nutritional value, antioxidants, and natural color to the processed foods. However, little information regarding the functional properties of the sweet potato flour is available. In this study, the genetic diversity in the physiochemical, nutritional and antioxidant properties of wholemeal flour from seven sweet potato varieties were investigated. The total phenolic content of the free and bound fractions ranged from 13.85 to 90.74 mg GAE/100 g and from 5.07 to 24.29 mg GAE/100 g, respectively. The average protein content of sweet potato was 5.41 g /100 g ranging from 3.40 to 8.60 g/100 g DW. The total amino acid content averaged 45.13 mg/g DW. The average contents of 12 mineral elements were in the order of K>P>Ca>Mg>Mn>Fe>Zn>Cu>Ni>Se>Cr>Cd. K and P contents were the highest among all accessions, which were positively correlated with most of the other minerals. The average starch content of sweet potato was 53.90g/100g DW, ranging from 31.68 % to 64.90%. The peak viscosity, hot paste viscosity and cold paste viscosity was in the range of 90.7 to 318.8 rapid visco unit (RVU), 77.3 to 208.3 RVU, and 102.6 to 272.7 RVU, respectively. The hardness values and cohesiveness varied among different sweet potatoes, with a range of 8.20 to 18.48 g and 0.22 to 0.68, respectively. The gelatinization onset, peak, conclusion temperatures and enthalpy were in the ranges of 59.39 to 71.91℃, 70.19 to 88.40℃, 78.98 to 95.79℃, 1.85 to 5.65J/g, respectively.